Dynamika władzy w powojennych Chinach. Próba analizy teoretycznej - Dawid Rogacz, Dawid Rogacz (Człowiek i Społeczeństwo, 2016)
The aim of this paper is to make an attempt to analyze the dynamics of thr political power in People’s Republic of China, using the conceptual apparatus of Leszek Nowak’s non-Marxian historical materialism. By means of application of his first model of the dynamics of power, I am going to generalize in theoretical manner main political changes in post-war China: from foundation of PRC, through Cultural Revolution and Opening Reforms up to the Chinese politics after 1989. Conducted analysis will allow me to make three wide-ranging predictiions concerning further development of China in the field of politics, economy and ideology.